Highly-doped silicon-based negative electrode plate, lithium ion battery and preparation method of highly-doped silicon-based negative electrode plate

By designing a gradient-distributed composite negative electrode material layer and a stable SEI film in lithium-ion batteries, the volume change problem of the silicon-based negative electrode is solved, the energy density and cycle stability of the battery are improved, and the safety is enhanced.

CN120637388APending Publication Date: 2025-09-12XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510802858.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

The volume change of silicon-based negative electrode during charging and discharging causes pulverization and separation from the current collector, resulting in poor conductivity of the negative electrode, safety issues, capacity loss and limited battery life cycle. In addition, the increase in the hybrid anode potential of Si/graphite composite batteries leads to a decrease in the potential and power density of the entire battery.

Method used

By designing the gradient distribution of the first graphite active material and the silicon-based negative electrode material in the composite negative electrode material layer, and combining the fast-charging graphite active material and the stable SEI film, a highly flexible SEI film is formed through gradient distribution and high-rate formation, which alleviates volume expansion and increases the delithiation depth of silicon.

Benefits of technology

It improves the energy density and first coulombic efficiency of lithium-ion batteries, reduces the battery expansion rate, and enhances the cycle stability and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637388A_ABST
    Figure CN120637388A_ABST
Patent Text Reader

Abstract

The invention provides a highly-doped silicon-based negative electrode plate, a lithium ion battery and a preparation method, and relates to the technical field of lithium ion batteries, the highly-doped silicon-based negative electrode plate comprises a current collector, a composite negative electrode material layer and a graphite negative electrode active material layer; two sides of the current collector are respectively coated with a composite negative electrode material layer; the composite negative electrode material layer is coated with a graphite negative electrode active material layer; wherein the composite negative electrode material layer comprises a first graphite active material and a silicon-based negative electrode material; along the direction far away from the current collector, the mass fraction of the first graphite active material is reduced from 75-95% to 5-25%, and the mass fraction of the silicon-based negative electrode material is increased from 5-25% to 75-95%. The lithium removal depth of silicon can be improved, the energy density of the battery is effectively improved, the volume expansion of the silicon-based negative electrode battery in the cycle process is relieved, and the first coulombic efficiency and the cycle stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a highly mixed silicon-based negative electrode sheet, a lithium ion battery and a preparation method thereof. Background Art

[0002] In recent years, the demand for energy storage technology has grown rapidly, placing higher demands on the high energy / power density, safety, and durability of lithium-ion batteries. Silicon or silicon-containing materials are considered to be one of the most promising candidate materials for the negative electrode of next-generation lithium-ion batteries due to their ultra-high theoretical capacity, low cost, and abundant sources. However, the volume change of the silicon negative electrode during the charge and discharge process can cause the silicon material to pulverize and separate from the current collector, resulting in poor conductivity of the negative electrode, which in turn leads to safety issues, capacity loss, and a limited battery life cycle. Currently, commercial Si / graphite composite batteries can provide higher energy density, and the addition of graphite can also alleviate the volume effect of the electrode to a certain extent. However, as the Si content increases, the potential of the mixed anode gradually increases, which will lead to a decrease in the overall potential and power density of the entire battery, and will also reduce the battery's first coulombic efficiency and cycle stability to a certain extent.

[0003] In view of this, this invention is proposed. Summary of the Invention

[0004] The present invention aims to provide a highly mixed silicon-based negative electrode sheet, a lithium-ion battery, and a preparation method. By designing a gradient distribution of the first graphite active material content and the silicon-based negative electrode material content in the composite negative electrode material layer, the present invention can increase the depth of silicon delithiation, effectively improving the battery's energy density and mitigating volume expansion during cycling of silicon-based negative electrode batteries, thereby enhancing the battery's initial coulombic efficiency and cycling stability.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a highly mixed silicon-based negative electrode sheet, comprising a current collector, a composite negative electrode material layer and a graphite negative electrode active material layer;

[0007] Both sides of the current collector are coated with composite negative electrode material layers respectively;

[0008] The composite negative electrode material layer is coated with a graphite negative electrode active material layer;

[0009] Wherein, the composite negative electrode material layer includes a first graphite active material and a silicon-based negative electrode material;

[0010] In the direction away from the current collector, based on the total mass of the first graphite active material and the silicon-based negative electrode material as 100%, the mass fraction of the first graphite active material decreases from 75%-95% to 5%-25%, and the mass fraction of the silicon-based negative electrode material increases from 5%-25% to 75%-95%.

[0011] Furthermore, based on the above technical solution, the composite negative electrode material layer comprises 10-90 parts by mass of the first graphite active material and 10-90 parts by mass of the silicon-based negative electrode material;

[0012] And / or, the first graphite active material has a particle size distribution of: D10 = 3.0 to 7.0 μm, D50 = 12.0 to 18.0 μm, a particle size D90 = 30.0 to 35.0 μm, and a true density of 2.20 g / cm 3 to 2.26g / cm 3 ;

[0013] And / or, the silicon-based negative electrode material has a particle size distribution of: D10 = 2.0 to 5.5 μm, D50 = 6.0 to 10.5 μm, a particle size D90 = 12.0 to 16.0 μm, and a true density of 1.50 g / cm 3 to 2.10g / cm 3 ;

[0014] And / or, the graphite negative electrode active material layer includes a second graphite active material, the second graphite active material is a fast-charging graphite active material, and the fast-charging graphite active material includes natural graphite particles or artificial graphite particles with a fast-charging capacity of 4-6C;

[0015] The specific capacity of the first graphite active material and the second graphite active material are both 340-360 mAh / g;

[0016] The particle size distribution of the second graphite active material is: D10 = 3.0 to 8.5 μm, D50 = 8.0 to 12.0 μm, particle size D90 = 16.0 to 24.1 μm, and true density is 2.24 g / cm 3 to 2.26g / cm 3 .

[0017] Furthermore, based on the above technical solution, the silicon-based material includes at least one of nano-silicon, micro-silicon, porous silicon, amorphous silicon, silicon alloy, silicon oxide or silicon-carbon composite material;

[0018] and / or, the first graphite active material comprises natural graphite particles or artificial graphite particles having a fast charging capability of 1.2-2.5C;

[0019] and / or, the current collector comprises copper foil;

[0020] And / or, the thickness of the highly doped silicon-based negative electrode sheet is 85-100 μm;

[0021] and / or, the thickness of the current collector is 6 μm;

[0022] and / or, the thickness of the composite negative electrode material layer is 60-130 μm;

[0023] And / or, the thickness of the graphite negative electrode active material layer is 10-20 μm.

[0024] The present invention also provides a method for preparing the highly doped silicon-based negative electrode sheet as described above, comprising the following steps:

[0025] S1: uniformly mixing a first graphite active material and a silicon-based negative electrode material to obtain a composite negative electrode material; adding a first conductive agent, a first binder, a second conductive agent, and a second binder to the composite negative electrode material and dispersing them to obtain a first negative electrode slurry;

[0026] S2: placing an aqueous binder in deionized water and stirring to obtain a negative electrode glue solution; adding a first conductive agent, a second graphite active material, and a second binder to the negative electrode glue solution and dispersing them to obtain a second negative electrode slurry;

[0027] S3: Apply the first negative electrode slurry to the upper and lower surfaces of the current collector, dry, roll and shape it to obtain a negative electrode sheet coated with a composite negative electrode material layer; then apply the second negative electrode slurry to the upper and lower surfaces of the negative electrode sheet coated with the composite negative electrode material layer, dry, roll and die-cut it to obtain a highly mixed silicon-based negative electrode sheet.

[0028] Furthermore, based on the above technical solution, step S1 includes: uniformly mixing the first graphite active material and the silicon-based negative electrode material to obtain a composite negative electrode material; sequentially adding a first conductive agent, a first binder, a second conductive agent, and deionized water to the composite negative electrode material, performing high-speed dispersion, and then adding the second binder, and uniformly dispersing to obtain a first negative electrode slurry;

[0029] Step S2 includes: placing an aqueous binder in deionized water and stirring to obtain a negative electrode glue; adding a first conductive agent to the negative electrode glue and dispersing it at high speed to obtain a negative electrode conductive glue; adding a second graphite active material to the negative electrode conductive glue and dispersing it at high speed, and then adding a second binder and dispersing it evenly to obtain a second negative electrode slurry.

[0030] Furthermore, based on the above technical solution, the first conductive agent includes one or more of conductive carbon black, acetylene black, and Ketjen black;

[0031] And / or, the first adhesive includes a propylene polymer or a styrene-butadiene rubber adhesive;

[0032] And / or, the second conductive agent includes one or more of single-walled carbon nanotubes, carbon fibers, and graphene;

[0033] And / or, the second adhesive includes a styrene-butadiene rubber adhesive;

[0034] and / or, the aqueous binder comprises carboxymethyl cellulose;

[0035] And / or, in step S1, the amount of the first conductive agent added is 0.5%-1.0% of the mass of the composite negative electrode material;

[0036] And / or, in step S1, the amount of the first binder added is 2.3%-6% of the total mass of the first conductive agent and the composite negative electrode material;

[0037] And / or, in step S1, the amount of the second conductive agent added is 0.05%-0.1% of the total mass of the first conductive agent and the composite negative electrode material;

[0038] And / or, in step S1, the amount of the second binder added is 1.0-2.5% of the total mass of the first conductive agent, the second conductive agent, the first binder, deionized water and the composite negative electrode material;

[0039] And / or, in step S1 and step S2, the rotation speed of the high-speed dispersion is 2000-4000 rpm, and the time is 5-10 minutes.

[0040] Furthermore, based on the above technical solution, the viscosity of the first negative electrode slurry is 4000-8000 mPa·s, and the solid content is 40%-65%;

[0041] and / or, the viscosity of the second negative electrode slurry is 2500-4000 mPa·s, and the solid content is 35%-45%; in step S2, the solid content of the negative electrode glue is 1.0-2.5%;

[0042] And / or, in step S2, the amount of the first conductive agent added is 0.5-2.0% by mass of the negative electrode glue;

[0043] And / or, in step S2, the amount of the second graphite active material added accounts for 95.3%-96.2% of the mass of the negative electrode conductive glue;

[0044] And / or, in step S2, the amount of the second binder added accounts for 1.6-2.5% of the total mass of the second graphite active material and the negative electrode conductive paste;

[0045] And / or, in step S3, the coating surface density of the first negative electrode slurry is 86-190 g / cm2 , the drying temperature of the first negative electrode slurry is 60-80°C;

[0046] And / or, in step S3, the coating surface density of the second negative electrode slurry is 35-45 g / cm 2 The drying temperature of the first negative electrode slurry is 70-85°C.

[0047] The present invention also provides a lithium-ion battery comprising a positive electrode sheet, the highly mixed silicon-based negative electrode sheet as described above, a separator, an electrolyte and a shell.

[0048] The present invention also provides a method for preparing the lithium-ion battery as described above, comprising the following steps:

[0049] The positive electrode sheet prepared from the positive electrode material and the above-mentioned high-mixed silicon-based negative electrode sheet are stacked, assembled, baked, injected, formed, and divided into volumes in the order of diaphragm-negative electrode-diaphragm-positive electrode to produce a high-mixed silicon-based negative electrode lithium-ion battery.

[0050] Furthermore, based on the above technical solution, the formation includes: charging at 0.1-0.5C for 7-24 minutes, standing for 5 minutes, charging at 0.1-0.5C for 117-127 minutes, and forming an SOC of 35%-40%.

[0051] The present invention provides a highly mixed silicon-based negative electrode sheet, a lithium-ion battery, and a preparation method, which have the following beneficial effects:

[0052] 1. The present invention provides a method for preparing a highly mixed silicon-based negative electrode sheet, thereby obtaining a negative electrode sheet containing a gradient-distributed composite negative electrode active material layer. The gradient-distributed composite negative electrode active material layer has a higher silicon content on the side close to the SEI membrane, which makes the silicon close to the SEI membrane delithiate earlier than graphite during the discharge process, thereby increasing the delithiation depth of silicon to a certain extent and improving the discharge capacity and energy density of the battery.

[0053] 2. The negative electrode sheet provided by the present invention also includes a graphite negative electrode active material layer, which can form a stable and tough SEI film during the formation process, effectively alleviating the problems of SEI deformation, rupture and regeneration caused by volume expansion of silicon-based negative electrode lithium-ion batteries during the cycle; the silicon-based material with a higher content is in the middle of the graphite material, and the graphite has high lubricity. After the silicon-based material is embedded with lithium and expands, the middle layer is squeezed toward the outer graphite layer and partially embedded in the graphite layer structure. Under high pressure, it can buffer the large amount of stress brought by silicon, thereby reducing the overall expansion rate of the electrode.

[0054] 3. The present invention also provides a method for preparing a high-energy-density lithium-ion battery, which produces a highly mixed silicon-based negative electrode lithium-ion battery with high initial coulombic efficiency, low expansion and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0056] Figure 1 This is a schematic diagram of the simulated structure of one side of the highly doped silicon-based negative electrode sheet provided by the present invention;

[0057] icon:

[0058] 1. Current collector; 2. Composite negative electrode material layer; 2-1. First graphite active material; 2-2. Silicon-based negative electrode material; 3. Graphite negative electrode active material layer. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. The process parameters for which specific conditions are not specified in the following examples are generally in accordance with conventional conditions.

[0060] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to form one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed in the present invention.

[0061] According to a first aspect of the present invention, there is provided a highly doped silicon-based negative electrode sheet comprising a current collector 1, a composite negative electrode material layer 2 and a graphite negative electrode active material layer 3;

[0062] Both sides of the current collector 1 are coated with a composite negative electrode material layer 2;

[0063] The composite negative electrode material layer 2 is coated with a graphite negative electrode active material layer 3;

[0064] Wherein, the composite negative electrode material layer includes a first graphite active material 2-1 and a silicon-based negative electrode material 2-2;

[0065] In the direction away from the current collector, with the total mass of the first graphite active material 2-1 and the silicon-based negative electrode material 2-2 as 100%, the mass fraction of the first graphite active material 2-1 decreases from 75%-95% (for example, 78%, 80%, 82%, 85%, 87%, 90%, 93%, etc.) to 5%-25% (for example, 7%, 10%, 15%, 20%, 23%, etc.), and the mass fraction of the silicon-based negative electrode material 2-2 increases from 5%-25% (for example, 7%, 10%, 15%, 20%, 23%, etc.) to 75%-95% (for example, 78%, 80%, 82%, 85%, 87%, 90%, 93%, etc.).

[0066] Specifically, as the current collector moves away from the current collector, the content of the first graphite active material and the content of the silicon-based negative electrode material exhibit a gradient distribution, with the first graphite active material gradually decreasing and the content of the silicon-based negative electrode material gradually increasing. This invention can increase the depth of silicon delithiation, effectively improving the battery's energy density and mitigating the volume expansion of silicon-based negative electrode batteries during cycling, thereby improving the battery's initial coulombic efficiency and cycling stability.

[0067] Specifically, a layer of graphite negative electrode active material layer is coated on the surface of the composite negative electrode active material layer. The material layer is relatively thin and mainly serves as a carrier for precipitating the SEI film. Graphite has high lubricity. After the silicon-based material is embedded with lithium and expands, it is squeezed toward the outer graphite layer and partially embedded in the graphite layer structure. Under high pressure, it can buffer the large amount of stress brought by silicon, thereby reducing the overall expansion rate of the electrode. The SEI film formed by high-rate formation has strong flexibility and is strong enough, which effectively alleviates the problems of SEI deformation, rupture and regeneration caused by volume expansion of silicon-based negative electrode lithium-ion batteries during the cycle process. During the discharge process, the potential of the negative electrode gradually increases. The delithiation potential of graphite is lower than that of silicon. Graphite delithiation is first, and silicon delithiation is later. Generally speaking, there are still some lithium ions that have not been released at the silicon negative electrode in the low voltage range. The present invention utilizes a gradient electrode design to match short-time high-rate formation. Due to the concentration polarization of lithium ion diffusion, the silicon close to the SEI film side can release more lithium ions during the discharge process, which can increase the delithiation depth of silicon to a certain extent, thereby improving the discharge capacity and energy density of the battery.

[0068] As an optional embodiment of the present invention, the composite negative electrode material layer includes, by mass, 10-90 parts (e.g., 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, etc.) of a first graphite active material and 10-90 parts (e.g., 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, etc.) of a silicon-based negative electrode material.

[0069] Specifically, due to the gradient distribution of the composite negative electrode active material layer and the coating of a graphite negative electrode active material layer on the surface of the composite negative electrode active material layer, the material layer is relatively thin and mainly serves as a carrier for precipitating the SEI film, and graphite has high lubricity. After the silicon-based material is embedded in lithium and expands, it is squeezed toward the outer graphite layer and partially embedded in the graphite layer structure. Under high pressure, it can buffer the large amount of stress brought by silicon, thereby reducing the overall expansion rate of the electrode; the SEI film formed by high-rate formation has strong flexibility and is strong enough, which effectively alleviates the problems of SEI deformation, rupture and regeneration caused by the volume expansion of silicon-based negative electrode lithium-ion batteries during the cycle process. Therefore, even if the content of silicon-based negative electrode material is too high, the present invention can alleviate the expansion to a certain extent.

[0070] As an optional embodiment of the present invention, the particle size distribution of the first graphite active material is: D10 = 3.0 to 7.0 μm (for example, 4 μm, 5 μm, 6 μm, etc.), D50 = 12.0 to 18.0 μm (for example, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, etc.), particle size D90 = 30.0 to 35.0 μm (for example, 31 μm, 32 μm, 33 μm, 34 μm, etc.), and true density is 2.20 g / cm 3 to 2.26g / cm 3 (For example, 2.21g / cm 3 , 2.22g / cm 3 , 2.23g / cm 3 , 2.24g / cm 3 , 2.25g / cm 3 wait);

[0071] The particle size distribution of the silicon-based negative electrode material is: D10 = 2.0 to 5.5 μm (such as 3 μm, 4 μm, 5 μm, etc.), D50 = 6.0 to 10.5 μm (such as 7 μm, 8 μm, 9 μm, 10 μm, etc.), particle size D90 = 12.0 to 16.0 μm (such as 13 μm, 14 μm, 15 μm, etc.), and true density is 1.50 g / cm 3 to 2.10g / cm 3 (For example, 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 wait).

[0072] Specifically, the present invention utilizes the difference in density between silicon-based materials and graphite active materials and the difference in solvent volatilization rate with temperature to form a composite negative electrode active material layer with a non-uniform gradient distribution. The density of graphite is greater than that of silicon-based materials, and the silicon-based material in the coating tends to diffuse to the surface of the electrode. Therefore, by controlling the drying temperature and the solid content of the slurry, the concentration of the graphite active material from the current collector to the electrode surface is reduced, and the concentration of the silicon-based material from the current collector to the electrode surface is increased.

[0073] Furthermore, graphite with larger particle sizes has a higher tap density, which means that more active materials can be accommodated in the same volume, thereby increasing the volumetric energy density of the battery; the slurry viscosity of large-particle graphite is relatively low, which helps to reduce the difficulty of coating and makes the coating process simpler; large-particle graphite can form a tighter electrode, thereby increasing the compaction density and increasing the energy density of the battery; the size of the graphite particle size will affect the initial charge and discharge efficiency. Due to its higher compaction density, large-particle graphite can more effectively accommodate lithium ions, thereby increasing the initial charge efficiency. However, due to its larger specific surface area, small-particle graphite will form a more stable SEI film, thereby improving the coulombic efficiency; large-particle graphite has relatively good cycle stability, but due to its higher compaction density, it may cause the battery to expand more after long-term use, affecting the cycle life; the particle size of silicon-based negative electrode materials will also affect the rate performance, and small-sized silicon has better rate performance.

[0074] As an optional embodiment of the present invention, the silicon-based material includes at least one of nano-silicon, micron-silicon, porous silicon, amorphous silicon, silicon alloy, silicon-oxygen compound or silicon-carbon composite material;

[0075] The first graphite active material includes natural graphite particles or artificial graphite particles having a fast charging capacity of 1.2-2.5C (such as 1.4C, 1.6C, 1.8C, 2.0C, 2.2C, 2.4C, etc.);

[0076] The current collector includes copper foil.

[0077] As an optional embodiment of the present invention, the graphite negative electrode active material layer includes a second graphite active material, and the second graphite active material is a fast-charging graphite active material. The fast-charging graphite active material includes natural graphite particles or artificial graphite particles with a fast charging capacity of 4-6C (such as 4.2C, 4.4C, 4.6C, 4.8C, 5C, 5.4C, 5.6C, 5.8C, etc.).

[0078] Specifically, the presence of the fast-charging graphite active material layer and the high-rate current formation can form a stable and highly flexible SEI film on the surface of the graphite negative electrode. The SEI film has sufficient toughness to resist the large volume expansion when silicon is embedded with lithium, thereby improving the cycle stability and safety performance of the battery.

[0079] As an optional embodiment of the present invention, the specific capacity of the first graphite active material and the second graphite active material are both 340-360 mAh / g.

[0080] As an optional embodiment of the present invention, the particle size distribution of the second graphite active material is: D10 = 3.0 to 8.5 μm (for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc.), D50 = 8.0 to 12.0 μm (for example, 9 μm, 9.5 μm, 10 μm, 11 μm, 11.5 μm, etc.), particle size D90 = 16.0 to 24.1 μm (for example, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, etc.), and the true density is 2.24 g / cm 3 to 2.26g / cm 3 (For example, 2.245g / cm 3 , 2.25g / cm 3 , 2.255g / cm 3 wait).

[0081] Specifically, the D50 of the second graphite active material is smaller than that of the first graphite active material. Due to the larger specific surface area, small-particle graphite will form a more stable SEI film, alleviating the SEI rupture and repeated regrowth caused by the expansion of lithium insertion in the silicon-based negative electrode; the smaller the graphite particle size, the larger the specific surface area, which helps to reduce the current density of the electrode, reduce the polarization of the electrode, and provide more lithium ion diffusion channels, thereby shortening the migration path and reducing the diffusion impedance.

[0082] As an optional embodiment of the present invention, the thickness of the highly doped silicon-based negative electrode sheet is 85-100 μm (such as 90 μm, 93 μm, 95 μm, 97 μm, etc.);

[0083] The thickness of the current collector is 6 μm;

[0084] The thickness of the composite negative electrode material layer is 60-130 μm (such as 70 μm, 80 μm, 90 μm, 100 μm, 11 μm, 120 μm, etc.). The thickness of the composite negative electrode material layer is directly related to the mixing amount of graphite and silicon. The higher the silicon content, the smaller the thickness.

[0085] The thickness of the graphite negative electrode active material layer is 10-20 μm (eg, 12 μm, 14 μm, 16 μm, 18 μm, etc.).

[0086] Specifically, the graphite negative electrode active material layer is relatively thin, and its main function is to form the SEI film and serve as a buffer layer for the expansion of silicon-based particles. The silicon-based material content close to the graphite negative electrode active material layer is the highest, so there is no need to add silicon-based negative electrode materials to the graphite active material layer.

[0087] According to a second aspect of the present invention, there is provided a method for preparing the highly doped silicon-based negative electrode sheet as described above, comprising the following steps:

[0088] S1: uniformly mixing a first graphite active material and a silicon-based negative electrode material to obtain a composite negative electrode material; adding a first conductive agent, a first binder, a second conductive agent, and a second binder to the composite negative electrode material and dispersing them to obtain a first negative electrode slurry;

[0089] S2: placing an aqueous binder in deionized water and stirring to obtain a negative electrode glue solution; adding a first conductive agent, a second graphite active material, and a second binder to the negative electrode glue solution and dispersing them to obtain a second negative electrode slurry;

[0090] S3: Apply the first negative electrode slurry to the upper and lower surfaces of the current collector, dry, roll and shape it to obtain a negative electrode sheet coated with a composite negative electrode material layer; then apply the second negative electrode slurry to the upper and lower surfaces of the negative electrode sheet coated with the composite negative electrode material layer, dry, roll and die-cut it to obtain a highly mixed silicon-based negative electrode sheet.

[0091] Specifically, in step S3 of the present invention, after the first negative electrode slurry and the second negative electrode slurry are coated, they are directly dried without standing and settling. This is because the slurry of the graphite and silicon mixed negative electrode will settle after standing, and the binder will float, resulting in uneven distribution of the slurry. After coating and drying, the active material is easy to fall off from the current collector.

[0092] As an optional embodiment of the present invention, step S1 includes: uniformly mixing a first graphite active material and a silicon-based negative electrode material to obtain a composite negative electrode material; sequentially adding a first conductive agent, a first binder, a second conductive agent, and deionized water to the composite negative electrode material, performing high-speed dispersion, and then adding a second binder. After uniform dispersion, a first negative electrode slurry is obtained;

[0093] Step S2 includes: placing an aqueous binder in deionized water and stirring to obtain a negative electrode glue; adding a first conductive agent to the negative electrode glue and dispersing it at high speed to obtain a negative electrode conductive glue; adding a second graphite active material to the negative electrode conductive glue and dispersing it at high speed, and then adding a second binder and dispersing it evenly to obtain a second negative electrode slurry.

[0094] As an optional embodiment of the present invention, the first conductive agent includes one or more of conductive carbon black (SP), acetylene black, and Ketjen black;

[0095] The first binder includes polyacrylic acid (PAA) or styrene-butadiene rubber binder (SBR);

[0096] The second conductive agent includes one or more of single-walled carbon nanotubes (SWCNTs), carbon fibers, and graphene;

[0097] The second binder includes a styrene-butadiene rubber (SBR) binder;

[0098] The aqueous binder includes carboxymethyl cellulose (CMC).

[0099] As an optional embodiment of the present invention, in step S1, the amount of the first conductive agent added is 0.5%-1.0% (such as 0.6%, 0.7%, 0.8%, 0.9%, etc.) of the mass of the composite negative electrode material;

[0100] In step S1, the amount of the first binder added is 2.3%-6% (such as 3%, 4%, 5%, etc.) of the total mass of the first conductive agent and the composite negative electrode material;

[0101] In step S1, the amount of the second conductive agent added is 0.05%-0.1% (such as 0.06%, 0.07%, 0.09%, etc.) of the total mass of the first conductive agent and the composite negative electrode material;

[0102] In step S1, the amount of the second binder added is 1.0-2.5% (e.g., 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, etc.) of the total mass of the first conductive agent, the second conductive agent, the first binder, deionized water and the composite negative electrode material.

[0103] As an optional embodiment of the present invention, the viscosity of the first negative electrode slurry is 4000-8000 mPa·s (e.g., 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, etc.), and the solid content is 40%-65% (e.g., 45%, 50%, 55%, 60%, etc.);

[0104] The viscosity of the second negative electrode slurry is 2500-4000 mPa·s (such as 3000 mPa·s, 3500 mPa·s, 3700 mPa·s, etc.), and the solid content is 35%-45% (such as 38%, 40%, 43%, etc.).

[0105] Specifically, the present invention limits the solid content of the first negative electrode slurry and the second negative electrode slurry because a suitable solid content helps to form a gradient distribution effect of the first graphite active material and the silicon-based negative electrode material in the composite negative electrode material layer. Specifically: the higher the solid content of the slurry, the greater the viscosity of the slurry, the worse the fluidity, and the poor stability of the slurry. It is difficult for the first graphite active material and the silicon-based negative electrode material to form a gradient distribution effect in the composite negative electrode material layer, and it is easy to diffuse and collapse after coating. In severe cases, it may cause stripes or edge shrinkage on the coating surface; on the contrary, the lower the solid content of the slurry, the better the fluidity, but it may cause large fluctuations during coating, which will not only affect the gradient distribution effect in the composite negative electrode material layer, but also make the composite negative electrode material layer have insufficient adhesion on the current collector, thereby making the prepared battery prone to bulging and cracking. Moreover, if the solid component is small, the binder and other components are relatively more, and the film structure formed after drying is not tight enough and is easy to peel off from the current collector.

[0106] As an optional embodiment of the present invention, in step S1 and step S2, the speed of the high-speed dispersion is 2000-4000 rpm (such as 2500 rpm, 3000 rpm, 3500 rpm, etc.), and the time is 5-10 min (such as 6 min, 8 min, 9 min, etc.).

[0107] As an optional embodiment of the present invention, in step S2, the solid content of the negative electrode glue is 1.0-2.5% (such as 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, etc.);

[0108] In step S2, the amount of the first conductive agent added is 0.5-2.0% (such as 0.7%, 1%, 1.3%, 1.5%, 1.7%, etc.) of the mass of the negative electrode glue;

[0109] In step S2, the amount of the second graphite active material added accounts for 95.3%-96.2% (e.g., 95.5%, 95.7%, 96%, etc.) of the mass of the negative electrode conductive glue;

[0110] In step S2, the added amount of the second binder accounts for 1.6-2.5% (such as 1.8%, 2.0%, 2.2%, 2.4%, etc.) of the total mass of the second graphite active material and the negative electrode conductive glue.

[0111] As an optional embodiment of the present invention, in step S3, the coating surface density of the first negative electrode slurry is 86-190 g / cm 2 (For example, 100g / cm 2 、120g / cm 2 、140g / cm 2 、160g / cm 2、180g / cm 2 The drying temperature of the first negative electrode slurry is 60-80°C (such as 62°C, 65°C, 70°C, 75°C, etc.);

[0112] Specifically, the present invention chooses to dry the first negative electrode slurry at a temperature of 60-80°C because if the temperature is too high, the solvent evaporates too quickly, and the dense graphite will also be carried to the end away from the current collector by the rapidly evaporating solvent, and cannot form a gradient distribution with the silicon-based particles. In addition, if the temperature is too high, it will cause cracking of the electrode; if the temperature is too low, the solvent evaporates slowly, and the low-density silicon particles cannot migrate to the section away from the current collector in time, and cannot form a gradient distribution with the graphite.

[0113] In step S3, the coating surface density of the second negative electrode slurry is 35-45 g / cm 2 (For example, 38g / cm 2 , 40g / cm 2 , 42g / cm 2 , 44g / cm 2 The drying temperature of the first negative electrode slurry is 70-85° C. (eg, 72° C., 75° C., 80° C., etc.).

[0114] Specifically, the present invention utilizes the difference in density between silicon-based materials and graphite active materials and the difference in solvent evaporation rate with temperature to form a composite negative electrode active material layer with a non-uniform gradient distribution. When the temperature is too high, the evaporation rate of the solvent becomes faster, and the high-density graphite particles will be concentrated more near one end of the current collector, while the low-density silicon-based particles are driven by the liquid to float up.

[0115] Furthermore, the higher the slurry solids content, the greater the viscosity and the worse the fluidity. If the temperature is too low, the gradient distribution of the graphite and silicon-based anodes cannot be achieved. If the temperature is too high, the electrode sheet will easily crack. Conversely, if the slurry solids content is low, although the slurry has good fluidity, it may lead to insufficient adhesion of the coating. Because the solid content is low and the binder and other ingredients are relatively high, the film layer formed after drying is not dense enough and easily peels off from the current collector.

[0116] According to a third aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, a highly mixed silicon-based negative electrode sheet as described above or a highly mixed silicon-based negative electrode sheet prepared by the method for preparing a highly mixed silicon-based negative electrode sheet as described above, a diaphragm, an electrolyte and a casing.

[0117] According to a fourth aspect of the present invention, there is provided a method for preparing the lithium-ion battery as described above, comprising the following steps:

[0118] The positive electrode sheet prepared from the positive electrode material and the high-mixed silicon-based negative electrode sheet as described above or the high-mixed silicon-based negative electrode sheet prepared by the preparation method of the high-mixed silicon-based negative electrode sheet as described above are stacked, assembled, baked, injected, formed, and divided into volumes in the order of diaphragm-negative electrode-diaphragm-positive electrode to produce a high-mixed silicon-based negative electrode lithium-ion battery.

[0119] As an optional embodiment of the present invention, the positive electrode material in the positive electrode sheet is a high-nickel ternary material;

[0120] The diaphragm is a commercially available 12 μm PP wet-process diaphragm;

[0121] The electrolyte is a lithium salt solution with a concentration of 1 mol / L.

[0122] The lithium salt is LiPF6, the solvent is a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, and the additives include fluoroethylene carbonate (FEC) and vinylene carbonate (VC);

[0123] FEC accounts for about 7.0 wt% of the electrolyte weight, and VC accounts for about 3.0 wt% of the electrolyte weight;

[0124] The formation comprises: placing the battery that has been injected and immersed for 24 hours in an environment with a pressure of 280KPa and a temperature of 45°C, charging at 0.1-0.5C (such as 0.2C, 0.3C, 0.4C, etc.) for 7-24min (10min, 12min, 14min, 16min, 18min, 20min, 22min, etc.), placing it on hold for 5min, and charging at 0.1-0.5C (such as 0.2C, 0.3C, 0.4C, etc.) for 117-127min (120min, 124min, 126min, etc.), and forming the SOC to 35%-40% (such as 36%, 37%, 38%, 39%, etc.).

[0125] Specifically, the most critical film-forming stage of the formation is the first stage. The SEI film formed by the high-rate formation in the first stage of the formation of the present invention has strong flexibility and is strong enough, which effectively alleviates the problems of SEI deformation, rupture and regeneration caused by the volume expansion of silicon-based negative electrode lithium-ion batteries during the cycle process.

[0126] Furthermore, if the formation rate is too high, the structure of the SEI film may become loose, and the transmission resistance of lithium ions in the SEI film may increase, thereby affecting the rate performance of the battery; if the formation rate is too high, the migration speed of lithium ions between the positive and negative electrodes may be too fast, resulting in some lithium ions not having enough time to embed into the negative electrode material, thereby causing the loss of active lithium, reducing the initial charge and discharge efficiency of the battery and capacity attenuation; in addition, it may also cause excessive side reactions between the electrode materials and the electrolyte inside the battery, accelerating the aging process of the battery.

[0127] The present invention will be further described in detail below with reference to specific examples and comparative examples.

[0128] Example 1

[0129] S1: Artificial graphite particles (fast charging capacity of 2.5C, specific capacity of 350mAh / g) and nano-silicon in a weight ratio of 4:6 are mixed evenly to obtain a composite negative electrode material; then, about 0.95% of conductive carbon black (SP) based on the weight of the composite negative electrode material is added to the obtained composite negative electrode material and mixed evenly, and then about 3% of polyacrylic acid (PAA), deionized water and 0.1% of single-walled carbon nanotubes (SWCNTs) based on the weight of the above-mentioned mixed material are added, and high-speed dispersion is carried out at a speed of 3000rpm for 10 minutes, and then about 1.4% of styrene-butadiene rubber (SBR) binder based on the weight of the above-mentioned mixed material is added to the above-mentioned slurry, and dispersed evenly to obtain a first negative electrode slurry. The viscosity of the first negative electrode slurry is 6235mPa·s and the solid content is 52.6%.

[0130] The particle size of artificial graphite is: D10 = 5.93 μm, D50 = 12.6 μm, particle size D90 = 31.4 μm, and true density is 2.24 g / cm 3 ;

[0131] Nano silicon particle size is: D10 = 5.21, D50 = 9.62 μm, particle size D90 = 15.88 μm, true density is 1.80 g / cm 3 .

[0132] S2: Carboxymethyl cellulose (CMC) as an aqueous binder is added to deionized water to prepare a negative electrode glue with a solid content of about 1.8 wt%. About 1.0% of a conductive agent containing conductive carbon black (SP) based on the weight of the negative electrode glue is added to the obtained negative electrode glue and dispersed at high speed to obtain a negative electrode conductive glue. About 95.8% of natural graphite particles as a negative electrode active material based on the weight of the negative electrode conductive glue are added to the obtained negative electrode conductive glue (fast charging capacity of 6C, specific capacity of 349 mAh / g, particle size: D10=4.52μm, D50=10.47μm, particle size D90=20.69μm, true density of 2.25g / cm3 ) and high-speed dispersed at a speed of 3000 rpm for 10 minutes, then an appropriate amount of deionized water was added to the above slurry to adjust the viscosity of the slurry, and then about 2.0% of a styrene-butadiene rubber (SBR) binder based on the weight of the above mixed material was added to the above slurry to obtain a second negative electrode slurry. The viscosity of the second negative electrode slurry was 2936 mPa·s and the solid content was 37.8%.

[0133] S3: The obtained first negative electrode slurry is evenly coated on the upper and lower surfaces of a copper foil with a thickness of 6 μm by extrusion coating, and then dried and roller-pressed to obtain a negative electrode sheet coated with a composite negative electrode material layer. The coating surface density is 100.1 g / cm 2 , the drying temperature is 65 ° C; then the second negative electrode slurry is evenly coated on the upper and lower surfaces of the above negative electrode sheet using extrusion coating, and the coating surface density is 40g / cm 2 After drying at 80°C, rolling and die-cutting, a highly mixed silicon-based negative electrode sheet with a heterogeneous gradient and a thickness of 90 μm was obtained.

[0134] The mass fraction of the artificial graphite particles in the composite negative electrode material layer is reduced from 85% to 15%, and the mass fraction of nano-silicon is increased from 15% to 85%.

[0135] The thickness of the composite negative electrode material layer is 75 μm;

[0136] The thickness of the graphite negative electrode active material layer was 15 μm.

[0137] Preparation of positive electrode

[0138] Polyvinylidene fluoride (PVDF) is mixed with solvent N-methylpyrrolidone (NMP) to prepare a positive electrode glue with a solid content of about 6 weight%. About 1.1 weight% of conductive carbon black (SP) and 0.5% of multi-walled carbon nanotubes (MWCNT) based on the weight of the positive electrode glue are added to the obtained positive electrode glue and dispersed at high speed to obtain a positive electrode conductive glue. About 97.2 weight% of high nickel ternary positive electrode material based on the weight of the positive electrode conductive glue is added to the obtained positive electrode conductive glue, and dispersed at high speed to obtain a positive electrode slurry with a viscosity of 7250mPa·s. The above-mentioned positive electrode slurry is evenly coated on the upper and lower surfaces of a carbon-coated aluminum foil with a thickness of 12μm, and after drying, rolling and die-cutting, a double-sided surface density of 530g / m 2 The positive electrode.

[0139] The prepared positive electrode sheet and the prepared highly mixed silicon-based negative electrode sheet are assembled into a lithium-ion battery, comprising the following steps:

[0140] The positive and negative electrode sheets are stacked, assembled, baked, injected, formed, and divided into different volumes in the order of separator-negative electrode-separator-positive electrode to produce a highly mixed silicon-based negative electrode lithium-ion battery. The electrolyte has a concentration of 1 mol / L, the lithium salt is LiPF6, the solvent is ethylene carbonate (EC) + dimethyl carbonate (DMC) + ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, and additives include fluoroethylene carbonate (FEC) and vinylene carbonate (VC), with FEC accounting for approximately 7.0% by weight of the electrolyte and VC accounting for approximately 3.0% by weight of the electrolyte. The formation process is as follows: the battery, which has been injected and immersed for 24 hours, is placed in an environment with a pressure of 280 kPa and a temperature of 45°C, charged at 0.1C for 7 minutes, left for 5 minutes, and then charged at 0.16C for 127 minutes, with a formation state of charge of 35%.

[0141] Example 2

[0142] The main difference between this embodiment and embodiment 1 is that the drying temperature of the first negative electrode slurry is 75° C., and the remaining steps and technical parameters are the same as those of embodiment 1.

[0143] Example 3

[0144] The main difference between this embodiment and embodiment 1 is that the drying temperature of the first negative electrode slurry is 60° C., and the remaining steps and technical parameters are the same as those of embodiment 1.

[0145] Example 4

[0146] The coating area density of the second negative electrode slurry in this example is 35g / cm 2 The high-doped silicon-based negative electrode sheet with a thickness of 88 μm was obtained by drying at 75° C., rolling, and die-cutting. The remaining steps and technical parameters were the same as those in Example 1.

[0147] Example 5

[0148] The coating area density of the second negative electrode slurry in this example is 45g / cm 2 The high-doped silicon-based negative electrode sheet with a thickness of 92 μm was obtained by drying at 83° C., rolling, and die-cutting. The remaining steps and technical parameters were the same as those in Example 1.

[0149] Example 6

[0150] The formation process of this embodiment is: charging at 0.1C for 24 minutes, resting for 5 minutes, charging at 0.16C for 117 minutes, and forming an SOC of 35%. The remaining steps and technical parameters are the same as those of Example 1.

[0151] Example 7

[0152] In this embodiment, the mass ratio of the first graphite active material to the silicon-based negative electrode material is 5:5, and the coating surface density of the first negative electrode slurry is 110 g / m 2 The remaining steps and technical parameters are the same as those in Example 1.

[0153] Example 8

[0154] In this embodiment, the mass ratio of the first graphite active material to the silicon-based negative electrode material is 7:3, and the coating surface density of the first negative electrode slurry is 90 g / m 2 The remaining steps and technical parameters are the same as those in Example 1.

[0155] Comparative Example 1

[0156] In this comparative example, there is no graphite negative electrode active material layer. Only the first negative electrode slurry is used to prepare the negative electrode sheet. The coating area density of the composite negative electrode material layer is 120 g / cm 2 The remaining steps and technical parameters are the same as those in Example 1.

[0157] Comparative Example 2

[0158] The first negative electrode slurry in this comparative example is a pure silicon-carbon composite material, and the coating surface density of the silicon-carbon material layer is 90 g / cm 2 The remaining steps and technical parameters are the same as those in Example 1.

[0159] Comparative Example 3

[0160] The first negative electrode slurry of this comparative example is pure graphite active material, and the remaining steps and technical parameters are the same as those of Example 1.

[0161] Comparative Example 4

[0162] The formation process adopted in this comparative example is: charging at 0.01C for 60 min, standing for 5 min, charging at 0.1C for 48 min, standing for 5 min, and charging at 0.3C for 62 min. The remaining steps and technical parameters are the same as those in Example 1.

[0163] Comparative Example 5

[0164] The main difference between this comparative example and Example 1 is that the viscosity of the first negative electrode slurry is 2000 mPa·s and the solid content is 35.2%. The remaining steps and technical parameters are the same as those in Example 1.

[0165] Comparative Example 6

[0166] Compared with Example 1, the main difference between this comparative example is that the viscosity of the first negative electrode slurry is 9000 mPa.s and the solid content is 65%. The remaining steps and technical parameters are the same as those of Example 1.

[0167] Comparative Example 7

[0168] The main difference between this comparative example and Example 1 is that the drying temperature of the first negative electrode slurry is 100° C., and the remaining steps and technical parameters are the same as Example 1.

[0169] Comparative Example 8

[0170] In this comparative example, a silicon-based negative electrode material is added to the graphite negative electrode active material layer, the mass ratio of the silicon-based negative electrode material to the second graphite active material is 2:8, the viscosity of the second negative electrode slurry is 3201 mPa.s, the solid content is 38.5%, and the remaining steps and technical parameters are the same as in Example 1.

[0171] Comparative Example 9

[0172] The main difference between this comparative example and Example 1 is that the formation process is as follows: the battery that has been injected and immersed for 24 hours is placed in an environment with a pressure of 280KPa and a temperature of 45°C, charged at 0.7C for 7 minutes, left for 5 minutes, and charged at 0.16C for 127 minutes, and the formation SOC is 35%.

[0173] Performance Testing

[0174] The electrochemical performance test of lithium-ion batteries is carried out. The specific test method is as follows:

[0175] 1. Charge at a constant current of 1C at 25℃±2℃ until the battery voltage reaches 4.25V, then switch to constant voltage charging. Stop charging when the current drops to 0.05C. Let it rest for 1 hour after charging. Discharge at a current of 1C at 25℃±2℃ until the battery voltage reaches 2.5V. Test the capacity retention rate and the expansion rate of the negative electrode sheet after 200 cycles, and calculate the initial coulombic efficiency.

[0176] Capacity retention rate after 200 times = 200th discharge capacity / cell BOL discharge capacity;

[0177] Negative electrode sheet full charge expansion rate = (negative electrode sheet thickness after full charge after the 200th cycle - negative electrode sheet thickness after full charge of the battery cell BOL) / (negative electrode sheet thickness after full charge of the battery cell BOL - foil thickness);

[0178] First coulombic efficiency = first discharge capacity of battery cell / first charge capacity of battery cell;

[0179] 2. The obtained negative electrode sheet was cut into small discs with a diameter of 12 mm and formed into a half-battery with a lithium sheet. The specific testing method was as follows: 1. Standing for 5 minutes, 2. 0.1C CC to 5mV, 3. Standing for 5 minutes, 4. 0.05C CC to 5mV; 5. Standing for 5 minutes, 6. 0.01C CC to 5mV; 7. Standing for 5 minutes, 8. 0.1C DC to 2V. The lithium removal specific capacity of the negative electrode sheet of each embodiment and comparative example was calculated.

[0180] After the test, the results are shown in Table 1 below:

[0181] Table 1

[0182]

[0183]

[0184] As can be seen from Table 1, Example 1 has a higher specific capacity for lithium removal than Examples 2 and 3. The drying temperature affects the gradient distribution of graphite and silicon in the composite negative electrode material layer. Higher or lower temperatures, or faster or slower drying speeds, can cause the low-density silicon-carbon material to not migrate to the end away from the current collector in a timely manner, or the high-density graphite to move away from the current collector due to the slow solvent drying rate. This causes the graphite and silicon to accumulate together, failing to achieve a gradient distribution effect, resulting in poor cycling stability. By utilizing a gradient electrode design, the silicon content near the SEI film is greater than the graphite content, allowing silicon to release more lithium ions and increasing the depth of silicon delithiation. The coulombic efficiency of Example 1 is higher than that of Comparative Example 1 and Examples 4 and 5, and within a certain range, as the fast-charging graphite negative electrode material layer increases, the full-charge expansion rate of the negative electrode sheet decreases, and the coulombic efficiency and 200-cycle capacity retention rate increase. Comparison of Example 1, Example 6 and Comparative Example 4 shows that the presence of the fast-charging graphite active material layer and the high-rate current formation can form a stable and highly flexible SEI film on the surface of the graphite negative electrode. The SEI film has sufficient toughness to resist the large volume expansion when silicon is embedded with lithium, thereby improving the cycle stability and safety performance of the battery; the full-charge expansion rate of the negative electrode sheet of Example 1 is lower than that of Comparative Examples 2 and 3, indicating that the mixture of graphite active material and silicon-based negative electrode material can prevent the expansion of the negative electrode sheet to a certain extent, thereby improving the cycle stability.

[0185] As can be seen from Table 1, compared with Example 1, in Comparative Example 5, since the viscosity of the first negative electrode slurry in Comparative Example 5 is 2000 mPa·s and the solid content is 35.2%, the solid content is low and the fluidity is large, resulting in poor gradient distribution effect of the prepared composite negative electrode material layer, and insufficient adhesion of the composite negative electrode material layer to the current collector, affecting the performance of the battery.

[0186] As can be seen from Table 1, compared with Example 1, in Comparative Example 6, the viscosity of the first negative electrode slurry is 9000 mPa.s, the solid content is 65%, and the solid content is too high, resulting in poor fluidity.

[0187] The first graphite active material and the silicon-based negative electrode material are difficult to form a gradient distribution effect in the composite negative electrode material layer, and are prone to diffusion and collapse after coating, thereby affecting the performance of the battery.

[0188] As can be seen from Table 1, compared with Example 1, in Comparative Example 7, since the drying temperature of the first negative electrode slurry in Comparative Example 7 is 100°C, the drying temperature is too high, the solvent evaporates too quickly, and the dense graphite will also be carried to the end away from the current collector by the rapidly evaporating solvent, and cannot form a gradient distribution with the silicon-based particles. In addition, the high temperature will cause the electrode to crack, thereby affecting the performance of the battery.

[0189] As can be seen from Table 1, compared with Example 1, in Comparative Example 8, since silicon-based negative electrode material is added to the graphite negative electrode active material layer in Comparative Example 8, the thickness of the graphite negative electrode active material layer is relatively thin. After the silicon-based negative electrode material is added, it not only fails to buffer the expansion of the silicon-based particles in the composite negative electrode material layer, but also aggravates the expansion of the silicon-based particles, thereby affecting the performance of the battery.

[0190] As can be seen from Table 1, compared with Example 1, the formation rate in the first stage of Comparative Example 9 is larger, resulting in a loose structure of the formed SEI film and an increase in the transmission resistance of lithium ions in the SEI film, thereby affecting the rate performance of the battery.

[0191] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A highly mixed silicon-based negative electrode sheet, characterized in that: It includes a current collector, a composite negative electrode material layer and a graphite negative electrode active material layer; Both sides of the current collector are coated with composite negative electrode material layers respectively; The composite negative electrode material layer is coated with a graphite negative electrode active material layer; Wherein, the composite negative electrode material layer includes a first graphite active material and a silicon-based negative electrode material; In the direction away from the current collector, based on the total mass of the first graphite active material and the silicon-based negative electrode material as 100%, the mass fraction of the first graphite active material decreases from 75%-95% to 5%-25%, and the mass fraction of the silicon-based negative electrode material increases from 5%-25% to 75%-95%.

2. The highly doped silicon-based negative electrode sheet according to claim 1, characterized in that: The composite negative electrode material layer comprises 10-90 parts by mass of a first graphite active material and 10-90 parts by mass of a silicon-based negative electrode material; And / or, the first graphite active material has a particle size distribution of: D10 = 3.0 to 7.0 μm, D50 = 12.0 to 18.0 μm, a particle size D90 = 30.0 to 35.0 μm, and a true density of 2.20 g / cm 3 to 2.26g / cm 3 ; And / or, the silicon-based negative electrode material has a particle size distribution of: D10 = 2.0 to 5.5 μm, D50 = 6.0 to 10.5 μm, a particle size D90 = 12.0 to 16.0 μm, and a true density of 1.50 g / cm 3 to 2.10g / cm 3 ; And / or, the graphite negative electrode active material layer includes a second graphite active material, the second graphite active material is a fast-charging graphite active material, and the fast-charging graphite active material includes natural graphite particles or artificial graphite particles with a fast-charging capacity of 4-6C; The specific capacity of the first graphite active material and the second graphite active material are both 340-360 mAh / g; The particle size distribution of the second graphite active material is: D10 = 3.0 to 8.5 μm, D50 = 8.0 to 12.0 μm, particle size D90 = 16.0 to 24.1 μm, and true density is 2.24 g / cm 3 to 2.26g / cm 3 .

3. The highly doped silicon-based negative electrode sheet according to claim 1, characterized in that: The silicon-based material includes at least one of nano-silicon, micro-silicon, porous silicon, amorphous silicon, silicon alloy, silicon oxide or silicon-carbon composite material; and / or, the first graphite active material comprises natural graphite particles or artificial graphite particles having a fast charging capability of 1.2-2.5C; and / or, the current collector comprises copper foil; And / or, the thickness of the highly doped silicon-based negative electrode sheet is 85-100 μm; and / or, the thickness of the current collector is 6 μm; and / or, the thickness of the composite negative electrode material layer is 60-130 μm; And / or, the thickness of the graphite negative electrode active material layer is 10-20 μm.

4. A method for preparing a highly doped silicon-based negative electrode sheet according to any one of claims 1 to 3, characterized in that: The steps include: S1: uniformly mixing a first graphite active material and a silicon-based negative electrode material to obtain a composite negative electrode material; adding a first conductive agent, a first binder, a second conductive agent, and a second binder to the composite negative electrode material and dispersing them to obtain a first negative electrode slurry; S2: placing an aqueous binder in deionized water and stirring to obtain a negative electrode glue solution; adding a first conductive agent, a second graphite active material, and a second binder to the negative electrode glue solution and dispersing them to obtain a second negative electrode slurry; S3: Apply the first negative electrode slurry to the upper and lower surfaces of the current collector, dry, roll and shape it to obtain a negative electrode sheet coated with a composite negative electrode material layer; then apply the second negative electrode slurry to the upper and lower surfaces of the negative electrode sheet coated with the composite negative electrode material layer, dry, roll and die-cut it to obtain a highly mixed silicon-based negative electrode sheet.

5. The method for preparing a highly doped silicon-based negative electrode sheet according to claim 4, wherein: Step S1 includes: uniformly mixing a first graphite active material and a silicon-based negative electrode material to obtain a composite negative electrode material; sequentially adding a first conductive agent, a first binder, a second conductive agent, and deionized water to the composite negative electrode material, performing high-speed dispersion, and then adding a second binder and uniformly dispersing to obtain a first negative electrode slurry; Step S2 includes: placing an aqueous binder in deionized water and stirring to obtain a negative electrode glue solution; adding a first conductive agent to the negative electrode glue solution and dispersing it at high speed to obtain a negative electrode conductive glue; A second graphite active material is added to the negative electrode conductive glue and dispersed at high speed, and then a second binder is added and dispersed evenly to obtain a second negative electrode slurry.

6. The method for preparing a highly doped silicon-based negative electrode sheet according to claim 5, characterized in that: The first conductive agent includes one or more of conductive carbon black, acetylene black, and Ketjen black; And / or, the first adhesive includes a propylene polymer or a styrene-butadiene rubber adhesive; And / or, the second conductive agent includes one or more of single-walled carbon nanotubes, carbon fibers, and graphene; And / or, the second adhesive includes a styrene-butadiene rubber adhesive; and / or, the aqueous binder comprises carboxymethyl cellulose; And / or, in step S1, the amount of the first conductive agent added is 0.5%-1.0% of the mass of the composite negative electrode material; And / or, in step S1, the amount of the first binder added is 2.3%-6% of the total mass of the first conductive agent and the composite negative electrode material; And / or, in step S1, the amount of the second conductive agent added is 0.05%-0.1% of the total mass of the first conductive agent and the composite negative electrode material; And / or, in step S1, the amount of the second binder added is 1.0-2.5% of the total mass of the first conductive agent, the second conductive agent, the first binder, deionized water and the composite negative electrode material; And / or, in step S1 and step S2, the rotation speed of the high-speed dispersion is 2000-4000 rpm, and the time is 5-10 minutes.

7. The method for preparing a highly doped silicon-based negative electrode sheet according to claim 5, characterized in that: The viscosity of the first negative electrode slurry is 4000-8000 mPa·s, and the solid content is 40%-65%; and / or, the viscosity of the second negative electrode slurry is 2500-4000 mPa·s, and the solid content is 35%-45%; in step S2, the solid content of the negative electrode glue is 1.0-2.5%; And / or, in step S2, the amount of the first conductive agent added is 0.5-2.0% by mass of the negative electrode glue; And / or, in step S2, the amount of the second graphite active material added accounts for 95.3%-96.2% of the mass of the negative electrode conductive glue; And / or, in step S2, the amount of the second binder added is 1.6-2.5% of the total mass of the second graphite active material and the negative electrode conductive paste; And / or, in step S3, the coating surface density of the first negative electrode slurry is 86-190 g / cm 2 , the drying temperature of the first negative electrode slurry is 60-80°C; And / or, in step S3, the coating surface density of the second negative electrode slurry is 35-45 g / cm 2 The drying temperature of the first negative electrode slurry is 70-85°C.

8. A lithium-ion battery, characterized in that: The invention comprises a positive electrode sheet, a highly mixed silicon-based negative electrode sheet as described in any one of claims 1 to 3 or a highly mixed silicon-based negative electrode sheet prepared by the method for preparing a highly mixed silicon-based negative electrode sheet as described in any one of claims 4 to 7, a diaphragm, an electrolyte and a shell.

9. A method for preparing a lithium-ion battery according to claim 8, characterized in that: The steps include: The positive electrode sheet prepared from the positive electrode material and the high-doped silicon-based negative electrode sheet as described in any one of claims 1 to 3 or the high-doped silicon-based negative electrode sheet prepared by the preparation method of the high-doped silicon-based negative electrode sheet as described in any one of claims 4 to 7 are stacked, assembled, baked, injected, formed, and capacity-divided in the order of diaphragm-negative electrode-diaphragm-positive electrode to produce a high-doped silicon-based negative electrode lithium-ion battery.

10. The method for preparing a lithium-ion battery according to claim 9, wherein: The formation comprises: charging at 0.1-0.5C for 7-24 minutes, resting for 5 minutes, and charging at 0.1-0.5C for 117-127 minutes, and the formation SOC is 35%-40%.

Citation Information

Patent Citations

  • Graphite / silicon gradient electrode material and preparation method and fast charging application thereof

    CN114156458A

  • Negative plate, preparation method thereof and lithium ion battery

    CN115528204A

  • Silicon-based negative electrode plate of high-energy-density lithium ion battery and preparation method of silicon-based negative electrode plate

    CN115732633A

  • Heterogeneous gradient high-silicon negative pole piece as well as preparation method and application thereof

    CN116960277A

  • Silicon composite material and preparation method thereof, negative pole piece, secondary battery and electric device

    CN119581504A